Exploring Edge-Based Segmentation Towards Automated Skin Lesion Diagnosis - Lau, Hui Keng; Chang, Jia Woei; Norhayati Daut; Asni Tahir; Erdah Samino; Mohd Hanafi Bin Ahmad Hijazi (American Scientific Publishers, 2018)
Automated medical diagnosis has many potentials and benefits to support healthcare. Therefore, there is growing number of research on this topic. There are many challenges before automated medical diagnosis is accepted by the healthcare industry and the public as a tool to facilitate healthcare professionals. In this paper, initial work on exploring edge-based segmentation algorithms to identify areas on an image that form the skin lesion is presented. Four edge-segmentation operators namely Canny, Prewitt, Sobel, and Roberts were tested using images from online image database. Experiments show results with mixed accuracy depending on the quality of image as well as the pattern of the skin lesions.